2009
DOI: 10.1007/s11999-009-0883-x
|View full text |Cite
|
Sign up to set email alerts
|

Do Successful Surgical Results after Operative Treatment of Long-bone Nonunions Correlate with Outcomes?

Abstract: Level III, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Patient-reported pain has been demonstrated to be greatly affected by fracture healing, and the vast majority of our cohort was likely healed by the 3-month time point. 15 There was no difference between groups in regard to distribution of genders, polytrauma status, or age. Albuquerque et al 16 reported on their cohort of 249 patients with tibial plateau fracture treated at an urban level 1 trauma center and similarly demonstrated no difference in age, gender, or polytrauma status between a lateral tibial plateau fracture group and a medial or bicondylar plateau fracture group.…”
Section: Discussionmentioning
confidence: 84%
“…Patient-reported pain has been demonstrated to be greatly affected by fracture healing, and the vast majority of our cohort was likely healed by the 3-month time point. 15 There was no difference between groups in regard to distribution of genders, polytrauma status, or age. Albuquerque et al 16 reported on their cohort of 249 patients with tibial plateau fracture treated at an urban level 1 trauma center and similarly demonstrated no difference in age, gender, or polytrauma status between a lateral tibial plateau fracture group and a medial or bicondylar plateau fracture group.…”
Section: Discussionmentioning
confidence: 84%
“…In situations where a determination could not be made, a CT scan was obtained to confirm union. 2,10,11,13 Intraoperative culture results and complications with wound infection identified during follow-up visits were recorded. Other follow-up complications, such as development of iliac crest graft site and surgical wound hematoma, wound dehiscence, wound breakdown, and malunion following revision, were also noted.…”
Section: Methodsmentioning
confidence: 99%
“…Nonunion is a devastating complication of a fracture, and can cause considerable patient morbidity. 1 The management of fracture nonunion is expensive with the estimated cost per case between £7000 and £79 000 ($10 000 to $114 000). [2][3][4][5] For every million people there are approximately 200 long-bone nonunions per year.…”
Section: Cite This Article: Bone Joint J 2016;98-b:534-41mentioning
confidence: 99%